4 У выражение −20(1,7x − 1) − (5 − 2,3x) - 8(0,2x − 4) и вычислите если х - 5/6

13Андрей1311 13Андрей1311    3   08.05.2020 13:13    0

Ответы
ekaterina2206 ekaterina2206  14.10.2020 11:27

при х=-5/6 ответ 74 3/4

при х=5/6 ответ 19 1/4

Пошаговое объяснение:

-20(1,7х-1)-(5-2,3х)-8(0,2х-4) = -34х+20-5+2,3х-1,6х+32=-33,3х+47

при х=-5/6 получаем

-33,3х+47=-33,3* (-5/6)+47=-33 3/10*(-5/6)+47=-333/10*(-5/6)+47=\frac{333*5}{10*6}+47=111/4+47=27 3/4+47=74 3/4

при х=5/6 получаем

-33,3х+47=-33,3*(5/6)+47=-333/10*(5/6)+47=-111/4+47=-27 3/4 + 47=19 1/4

ПОКАЗАТЬ ОТВЕТЫ
gkulgkuy gkulgkuy  14.10.2020 11:27

Пошаговое объяснение:

−20(1,7x − 1) − (5 − 2,3x) - 8(0,2x − 4) =-34х+20-5+2.3х-1.6х+32=-33.3х+47

-33.3*5\6+47=-33 3\10*5\6+47=-333\10*5\6+47=-111\4+47=-27.75+47=19.25=19 1/4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика